Manual screen-printing training for rice packaging labeling in Sidomulyo Village, Kutai Kartanegara Regency - Dita Andansari; Rony H.; Royke Vincentius Febriyana (Universitas Muhammadiyah Magelang, 2021)
Sidomulyo Village is one of the villages in Anggana District, Kutai Kartanegara Regency, East Kalimantan. To alleviate poverty in Sidomulyo Village, many millennial farmers have emerged, one of which is the Independent Farmer Youth Group with rice as a potential commodity. One of the agricultural products from this group is rice with several varieties including Mikongga and Mayas Rapak with each harvest reaching 3-4 tons/ha. The rice produced is very abundant but does not yet have a brand and label on the packaging. Based on this condition, the solution that can be offered to the Mandiri Tani Pemuda Group is training in making labels on plastic packaging for rice using manual screen-printing techniques. The method used is the lecture method and training in manual screen printing for plastic packaging for rice. The result of this training is that all participants can make rice packaging labels by manual screen printing.